Kajian Konservasi Gua Pawon Berdasarkan Kondisi Ekosistem - Deden Rizki Oktaviana; Ina Helena Agustina; Riswandha Risang Aji (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Pawon Cave is a natural cave located in the Citatah karst formation area, Rajamandala and is included in the list of geological nature reserves protected by the West Java Provincial Government. Pawon Cave is evidence of the existence of the Ancient Lake Bandung. However, at this time the vulnerability of the cave ecosystem and natural beauty began to change. There is quite an alarming phenomenon where the cave area has begun to be destroyed. It can be seen in the current physical form of the cave, where there is vandalism or there are graffiti on the walls of the cave carried out by irresponsible humans, not only that limestone mining which is currently still taking place in the area is also worrying because it can erode the rocks around the area. The existence of limestone processing also increases air pollution which is getting worse because can be seen that thick black smoke continues to float into the air caused by the processing. Therefore, the purpose of this research is "to identify the internal and external condition classes of Pawon Cave, as well as conservation efforts that will be carried out based on the identification of condition classes." This research uses quantitative and qualitative approach methods. With a scoring analysis method based on the results of field observations according to applicable parameters. Therefore, the conclusion of this research is that there are two components, namely the internal condition of the cave and the external condition of the cave. overall, the internal and external conditions of Pawon Cave are included in the moderate category. There are several factors that must be improved, such as the physical aspects of the cave, the type of ornamentation and the utilization of the area which will later be carried out in the direction of conservation in the Pawon Cave area. Abstrak. Gua pawon adalah gua alami yang berada di kawasan formasi karst Citatah, Rajamandala dan termasuk kedalam daftar cagar alam geologi yang dilindungi oleh Pemerintah Provinsi Jawa Barat. Gua Pawon menjadi bukti akan keberadaan Danau Purba Bandung. Namun pada saat ini kerentanan ekosistem gua serta keindahan alam mulai mengalami perubahan. Terdapat fenomena cukup mengkhawatirkan dimana Kawasan gua sudah mulai hancur. Terlihat pada bentuk fisik gua saat ini, dimana terdapat vandalisme atau terdapat coretan – coretan pada dinding gua yang dilakukan oleh manusia yang tidak bertanggung jawab tidak hanya itu penambangan batuan kapur yang saat ini masih terjadi di kawasan tersebut juga mengkhawatirkan karena dapat mengikis batuan di sekitar kawasan tersebut. Adanya pengolahan batuan kapur juga meningkatkan polusi udara yang semakin memburuk karena terlihat asap tebal hitam yang terus menerus mengapung ke udara yang diakibatkan dari pengolahan tersebut. Maka dari itu tujuan dalam penelitian ini yaitu “mengindentifikasi kelas kondisi internal dan eksternal Gua Pawon, serta upaya konservasi yang akan dilakukan berdasarkan identifikasi kelas kondisi.” Penelitian ini menggunakan metode pendekatan kuantitatif dan kualitatif. Dengan metode analisis skoring berdasarkan hasil dari observasi lapangan sesuai parameter yang berlaku. Maka dari itu kesimpulan dari penelitian ini terdapat dua komponen yaitu kondisi internal gua serta kondisi eksternal gua. secara keseluruhan kondisi internal dan eksternal Gua Pawon termasuk dalam kategori sedang. Dengan demikian terdapat beberapa faktor yang harus ditingkatkan, seperti aspek fisik gua, jenis ornamen dan pemanfaatan kawasan yang nantinya akan dilakukan arahan konservasi di Kawasan Gua Pawon.